Application of proteomic technologies to discover and identify biomarkers for periodontal diseases in gingival crevicular fluid: A review. Issue 3 (13th February 2014) - Tsuchida, Sachio; Satoh, Mamoru; Sogawa, Kazuyuki; Kawashima, Yusuke; Kado, Sayaka; Ishige, Takayuki; Beppu, Minako; Sawai, Setsu; Nishimura, Motoi; Kodera, Yoshio; Matsushita, Kazuyuki; Nomura, Fumio; et al.
<x xml:space="preserve">Abstract</x> Periodontal disease is a bacterial infection that destroys the gingiva and surrounding tissues of the oral cavity. In recent years, studies have shown a definite association between periodontal disease and other inflammatory conditions of the body. High‐throughput analysis of proteins has become possible with the development of MS technology. This breakthrough in proteome technology enables comparative studies of comprehensive protein expression and identification of protein. In case of periodontal disease, proteome analysis using 2DE, as well as gel‐free methods, has been reported. As a fluid lying in close proximity to periodontal tissue, the gingival crevicular fluid (GCF) is the principal target in the search for biomarkers of periodontal disease, because its protein composition may reflect the disease pathophysiology. Biochemical marker analysis of GCF is effective for objective diagnosis in the early and advanced stages of periodontal disease. Increasing numbers of recent reports have provided evidence that the proteomic approach is a promising tool for the discovery and identification of biochemical markers of periodontal disease. This search is of continuing interest in the field of experimental and clinical periodontal disease research. In this article, we summarize recent comprehensive proteomic studies aimed at discovering and identifying biomarkers of periodontal disease in GCF.